“For a sustainable future and democratic energy management”: The experience of building an alternative generation system in the city of Armstrong, Argentina - Garrido, Santiago (Estudios Avanzados, 2018)
The development of non-conventional renewable energies has been a central public agenda item in various Latin American countries for the past two decades. This importance can be explained by a multitude of factors, among which the most prominent is the context of energy crises experienced by several countries in the region, characterized by a common and primary element: the lack of diversification in their energy mixes.
Keywords: distributed generation; not conventional renewable energies; inclusive innovation; cooperativism